2015
DOI: 10.1134/s2079059715020070
|View full text |Cite
|
Sign up to set email alerts
|

Identification of new genes of nodule bacteria Sinorhizobium meliloti involved in the control of efficiency of symbiosis with alfalfa Medicago sativa

Abstract: Using a Tn5 mutagenesis in a Sinorhizobium meliloti strain CXM 1 105, we obtained three mutants with increased symbiotic efficiency with alfalfa. Our study demonstrated Tn5 insertions labeled two chromo some genes encoding 5 adenosylhomocysteine methylthioadenosine deaminase (mutant T4) and a protein belonging to the GntR family of transcription regulators (mutant M3) and a thiamine biosynthetic gene thiC, localized at megaplasmide 2 (mutant T795). Mutant T795 along with high symbiotic efficiency exhibited a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…PCR amplification was performed according to standard protocol (Weisburg et al, 1991). The obtained PCR fragments were isolated from agarose gel (Onishchuk et al, 2015) and sequenced using the ABI PRISM 3500xl (Applied Biosystems, Waltham, MA, USA). The sequences were compared with the sequence of the 16S rRNA gene of the strain Ch-13 B. subtilis, available in the GenBank database (Accession Number: MW050985).…”
Section: Identification Of Bacterial Strainsmentioning
confidence: 99%
“…PCR amplification was performed according to standard protocol (Weisburg et al, 1991). The obtained PCR fragments were isolated from agarose gel (Onishchuk et al, 2015) and sequenced using the ABI PRISM 3500xl (Applied Biosystems, Waltham, MA, USA). The sequences were compared with the sequence of the 16S rRNA gene of the strain Ch-13 B. subtilis, available in the GenBank database (Accession Number: MW050985).…”
Section: Identification Of Bacterial Strainsmentioning
confidence: 99%
“…PCR amplifications were performed using Pfu polymerase (Thermo Fisher Scientific, Waltham, MA, USA) according to standard protocol: initial denaturation at 95°C for 3 min, followed by 30 cycles at denaturation at 94°C for 30 s, primer annealing at 52°C for 30 s, extension at 72°C for 1 min, and a final extension lasting 4 min. PCR fragments were extracted from agarose gel (Onishchuk et al, 2015), with each PsMT-gene ligated with a nifH promoter. The obtained ligase mixtures were then used as a matrix in the PCR with primers nifH-F and MT1-R (for fusion with PsMT1) or with primers nifH-F and MT2-R (for fusion with PsMT2).…”
Section: Bacterial Strain Constructionmentioning
confidence: 99%
“… Kang et al (2019) revealed the potential of acdS gene to improve the growth of tomatoes and further tolerate salinity stress as a result of the regulation of secondary metabolite which goes with our study for being abundant in HR. mtaD gene induces plant growth, improves fruit ripening, and produce stimulates the production of the enzyme that belongs to the family of metallodependent hydrolases and involves phosphonates metabolism, together with various pesticides and herbicides ( Onishchuk et al, 2015 ). This gene is known for preventing the poisoning of crop plants caused by chemical pesticides and herbicides applied to farmland ( Loeschcke & Thies, 2015 ; Onishchuk et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%